Learner attitudes, student characteristics, and design feature as factors in blended learning effectiveness - Mahjudin, Mahjudin; Nurmawati, Nurmawati; Kristiawati, Indriana (COUNS-EDU: The International Journal of Counseling and Education, 2021)
ABTRACTSpecialists in the field of education have shown more and more interest in issues related to the learning process. Most of the studies produced by both psychologists and teachers have attempted to identify the factors that determine the learning process and to highlight possible relations among elements related to the quality of education, the teaching strategies used in the classroom and the quality of students performance This paper investigates the effectiveness of a blended learning environment through analyzing the relationship between learner attitudes, student characteristics, and design features. This paper explores the attitudes of learners towards blended learning and seeks to establish whether there are attitudinal differences with regard to gender and learner attitudes in different schools . Our results sho that blended learning is a venture worth undertaking by educational institutions but the attitude factor predicting learning performance needs to be established and therefore remains the focus of future work.